Layered infill area generation from triply periodic minimal surfaces for additive manufacturing. (February 2019) - Feng, Jiawei; Fu, Jianzhong; Lin, Zhiwei; Shang, Ce; Niu, Xiaomiao
Abstract: Compared with widely applied tessellation mesh or parametric spline surfaces, implicit surfaces are more suitable for representing models with complicated topology and geometry. Triply periodic minimal surface (TPMS) is a kind of charming implicit surface talented at designing porous structures. Layered infill area generation is the crucial task of process planning for additive manufacturing (AM). Generally, the constructed TPMS are open surfaces with zero thickness, which cannot be directly fabricated. In this work, a complete method is proposed to generate layered infill areas from TPMS for AM. Initially, based on the Marching Squares (MS) algorithm, the TPMS can be efficiently sliced into numerous unstructured line segments. Afterwards, an efficient sorting algorithm with a linear time complexity is developed by special data structures to generate ordered slicing contours. Eventually, in virtue of the demonstrated bidirectional-offset-union strategy, close polygons can be generated as layered infill areas for path planning procedure to manufacture TPMS structures with uniform wall thickness. Experimental results verify the effectiveness and merits of the proposed approach, which can also be expanded to fabricate other complicated implicit surfaces via AM technology. Highlights: A direct slicing algorithm of TPMS based on Marching Squares algorithm. An efficient sorting algorithm with a linear time complexity. Layered infill area with uniform wall thickness generation. Additively manufacture TPMS via SLM technology.